1999
DOI: 10.2337/diacare.22.1.65
|View full text |Cite
|
Sign up to set email alerts
|

Association between baseline plasma leptin levels and subsequent development of diabetes in Japanese Americans.

Abstract: Among Japanese Americans, increased baseline leptin levels are associated with increased risk of developing diabetes in men but not in women.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
123
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 155 publications
(133 citation statements)
references
References 0 publications
10
123
0
Order By: Relevance
“…Adiponectin is known as having anti-inflammatory, antiatherogenic and insulin-sensitizing properties 1 and it has been previously demonstrated that a low concentration of this hormone is an independent predictor of the metabolic syndrome 2 , coronary heart disease 3 and type 2 diabetes 4 . In the case of leptin, mixed results have been obtained, some studies observed that a high leptin concentration is a predictor of coronary events and type 2 diabetes independently of adiposity 5,6 while others showed that the association between leptin concentrations and these major chronic diseases is largely explained by concomitant variations in body weight or BMI 7,8 . It has been recently suggested that the leptin-to-adiponectin ratio could be a better marker of cardiometabolic alterations and insulin resistance than adiponectin or leptin alone 9,10 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adiponectin is known as having anti-inflammatory, antiatherogenic and insulin-sensitizing properties 1 and it has been previously demonstrated that a low concentration of this hormone is an independent predictor of the metabolic syndrome 2 , coronary heart disease 3 and type 2 diabetes 4 . In the case of leptin, mixed results have been obtained, some studies observed that a high leptin concentration is a predictor of coronary events and type 2 diabetes independently of adiposity 5,6 while others showed that the association between leptin concentrations and these major chronic diseases is largely explained by concomitant variations in body weight or BMI 7,8 . It has been recently suggested that the leptin-to-adiponectin ratio could be a better marker of cardiometabolic alterations and insulin resistance than adiponectin or leptin alone 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, some previous studies have found sex-related differences in the link between these adipose tissuederived hormones and the development of type 2 diabetes. In fact, the association between leptin concentrations and type 2 diabetes has been shown to be stronger in men than in women 5,6 while adiponectin concentrations would be more closely associated with type 2 diabetes in women than in men 12 . Sex-related differences have also been found in the relationship between blood concentrations of these adipocytokines and markers of cardiovascular risk 11,13 .…”
Section: Introductionmentioning
confidence: 99%
“…Instead, they reported that obesity and insulin resistance explained most of the association between leptin and subsequent diabetes risk. Other studies also suggest that abdominal adiposity may modulate the association between leptin and type 2 diabetes [9,12,14,15,25].…”
Section: Discussionmentioning
confidence: 99%
“…High levels of leptin have been shown to be independently associated with diabetes in some [8][9][10][11] but not all studies [7,[12][13][14][15]18]. Of these studies, only two were UK population based studies [7,10].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation